Effect of natural antioxidants on bond strength recovery of resin‐modified glass ionomers to the NaOCl‐affected pulp chamber dentin - Fereshteh Shafiei; Zahra Dehghani; Maryam S. Tavangar (Wiley, 2023)
Abstract Objective This study evaluated the effect of two natural antioxidants on the compromised bond strength of a resin‐modified glass ionomer (RMGI) to the sodium hypochlorite (NaOCl)‐affected pulp chamber dentin. Methods Forty‐two sound third molars were split into halves. The exposed pulp chamber dentin was ground to provide the flat dentin surfaces and divided into seven groups (n = 12), according to the solutions used for immersion: (1) Control, distilled water; (2) NaOCl, 5.25% NaOCl for 20 min; (3) NaOCl/Ethylenediaminetetraacetic acid (EDTA); 5.25% NaOCl for 20 min + 17% EDTA for 1 min; (4) NaOCl/TA, 5.25% NaOCl + 10% tanic acid (TA) for 5 min; (5) NaOCl/EDTA/TA, 5.25% NaOCl + 17% EDTA + 10% TA for 5 min; (6) NaOCl/PA, 5.25% NaOCl+ 10% proanthocyanidin for 5 min; and (7) NaOCl/EDTA/PA, 5.25% NaOCl+ 17% EDTA + 10% PA for 5 min. The RMGI was bonded on the treated dentin using a Tygon tube. After 24 h of storage, microshear bond strength (µSBS) was tested. Data in MPa were submitted to one‐way analysis of variance and Tamhane test. Results NaOCl significantly decreased the µSBS; NaOCl/EDTA and NaOCl/TA significantly increased the µSBS, higher than the control group (p < .05); and in the NaOCl/EDTA/TA group, the increased bond strength was at the level of the control group (p > .05). NaOCl/PA and NaOCl/EDTA/PA and NaOCl groups had comparable µSBS. Conclusion TA could be suggested to provide effective bonding of RMGI and immediate sealing of the pulp chamber dentin after NaOCl irrigation.